O federalismo cooperativo e a necessidade de efetivação do direito à saúde da pessoa com deficiência - Capuano, Tamara de Padua (2018)
The purpose of this study is to demonstrate that Brazilian federalism meets the contemporary, balanced or cooperative federative format based on the development and enrichment of constitutional democracy. The study of the division of powers reveals commands of cooperation between the components of the federation for the political progress and the pacification of regional asymmetries and controversies. Among these commands, we accentuate the common material competence of federal entities to take care of the protection and guarantee of people with disabilities, including their right to health, and the norm of article 23, single paragraph, of the Federal Constitution, which fosters the joint administrative activity of federal entities, aiming, in particular, to establish effective public policies for the provision of services of a social nature. For this interfederative cooperation there are valuable instruments provided for in the legal system available to federative entities. The use of these instruments is necessary to make compatible the principle of solidarity, resulting from common material competences, and the principle of substantial equality between federative entities, by dividing tasks between them according to their capabilities, correcting the asymmetries regional authorities. As a consequence, the balance of development and well-being at the national level and the realization of fundamental social rights in favor of the population will be promoted. Among these social rights, the right to health of persons with disabilities was investigated. Both the International Convention on the Rights of Persons with Disabilities and the Brazilian Law on the Inclusion of Persons with Disabilities adopted the social model of disability, aiming at maximum social inclusion of this group. In turn, their right to health does not only cover services of a biomedical nature, but also of a psychosocial nature and other obligations provided for in the Convention and Law 13.146/15, taking into account the specific needs of each person with disabilities, respecting the its uniqueness. Article 198 of the Federal Constitution requires the conjugation of efforts of all federal entities in public health actions and services. Due to the specificities of the right to health of persons with disabilities, their implementation depends on a targeted public policy provided by the joint and solidarity action of all federal entities, through the instruments of interfederative cooperation provided for in the legal system